Content mixing and membrane integrity during membrane fusion driven by pairing of isolated v-SNAREs and t-SNAREs - Nickel, Walter (The National Academy of Sciences, 1999)
Membrane bilayer fusion has been shown to be mediated by v- and t-SNAREs initially present in separate populations of liposomes and to occur with high efficiency at a physiologically meaningful rate. Lipid mixing was demonstrated to involve both the inner and the outer leaflets of the membrane bilayer. Here, we use a fusion assay that relies on duplex formation of oligonucleotides introduced in separate liposome populations and report that SNARE proteins suffice to mediate complete membrane fusion accompanied by mixing of luminal content. We also find that SNARE-mediated membrane fusion does not compromise the integrity of liposomes.